The Effectiviness of Hormone Growth Promoting Fertilizers on Increasing The Production of Arbuscular Mycorrhizal Fungi Spores - Ahmad Sadiqin; Faisal Danu Tuheteru; Asrianti Arif; Husna Husna; Albasri Albasri (Journal of Tropical Mycorrhiza, 2023)
Arbuscular Mycorrhizal Fungi (AMF) is one of the fungi that forms a mutualism symbiosis with plants where there is a mutually beneficial relationship between the two parties and acts as a biological fertilizer that needs to be reproduced.AMF propagation is strongly influenced by the availability of nutrients, growing media and host plants. The purpose of this study was to determine the application of hormone growth booster fertilizer to increase the production of arbuscular mycorrhizal fungi spores.This research was conducted at the Plastic House of the Indonesian Mycorrhizal Association (AMI) Southeast Sulawesi Branch and the Laboratory of the Department of Forestry, Faculty of Forestry and Environmental Sciences, Halu Oleo University, Kendari during September – November 2022.This study was arranged based on a Completely Randomized Factorial Design. which consists of 2 factors. The first factor: AMF type which consists of two levels, namely Glomus coronatum and Glomus claroideum. The second factor: Fertilizer application consisting of three levels, namely without fertilizer application (B0), 2, and 5 ml/pot fertilizer (B2) with 3 repetitions. So there are 18 treatment combinations. Each treatment unit contained 9 plants so that the total number of plants was 162 plants. The results of this study indicate that the interaction treatment of G. coronatum and G. claroideum without fertilizer application can give the best results in increasing the number of spores for 3 months and in the treatment of G. coronatum with a fertilizer dose of 2, 5 ml gave the best results for increasing the number of spores after drying. Treatment of G. claroideum with a dose of 5 ml of fertilizer gave the best results in increasing the number of spores after drying.